Biomass oxidation to formic acid in aqueous media using polyoxometalate catalysts – boosting FA selectivity by in-situ extraction - Albert, Jakob; Wasserscheid, Peter; Reichert, Jenny; Jess, Andreas; Brunner, Birgit (Energy and Environmental Science, 2015)
Herein, we report a remarkable finding that biomass oxidation to formic acid (FA) in water–organic biphasic reaction systems is far more selective than the same reaction in a monophasic aqueous media. While literature claims that the yield of FA from carbohydrates and biomass is limited to less than 68%, even for simple substrates such as glucose or glycerol, we demonstrate in this study that FA yields of up to 85% can be obtained from glucose. Using our biphasic reaction protocol, even raw lignocellulosic biomass, such as beech wood, leads to FA yields of 61%. This is realized by applying polyoxometalate H8PV5Mo7O40 as a homogeneous catalyst, oxygen as the oxidant and water as the solvent in the presence of a long-chain primary alcohol as an in-situ extracting agent. The new, liquid–liquid biphasic operation opens a highly effective way to produce pure FA, a liquid syngas equivalent, from wood in a robust, integrated, and low-temperature process.